Pengujian Perangkat Lunak Sistem Informasi Penilaian Mahasiswa dengan Teknik Boundary Value Analysis Menggunakan Metode Black Box Testing - Bagas Putra Pratama; Ilham Bagus Vitriadi Ristianto; Ismail Adi Prayogo; Nasrullah Nasrullah; Aries Saifudin (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2020)
In this student assessment application, if there is an error program, there will be losses for students and universities. Losses for students, if this application error occurs, then the assessment received by students will experience delays due to the difficulty in the process of calculating student grades and students will be late to receive an assessment. Losses for the university, if there is an error program on this application, the university will suffer losses if students want a rapid decline in grades but the university cannot calculate quickly and accurately. The method used in testing this application uses the black box method with boundary value analysis techniques. Boundary value analysis techniques test the quality of the application by showing that there are still some errors when entering data to be tested in the column to determine whether the input value is valid or not with the lower limit and the upper limit that has been determined. So the problems that occur can cause data stored in the database does not match the expected data. The test is carried out in the Student Rating form by testing the upper and lower limit values through several predetermined stages for each column contained in the form. Test results can be used as input to improve the application. The results of this test can provide a reference for testing the quality of student assessment applications by analyzing the functionality of the program that has been made in accordance with the expected results.